Bio-based adenine-containing high performance polyimide. (16th June 2017) - Hu, Jianghuai; Wang, Zhiping; Lu, Zheng; Chen, Chang; Shi, Meng; Wang, Jianbo; Zhao, Erjin; Zeng, Ke; Yang, Gang
Abstract: Because of the unique conjugated heterocyclic structure and the presence of reactive groups, adenine which can be obtained from biomass may be an ideal bio-based alternative structure of petroleum-based aromatic/heterocyclic structures. In this paper, the adenine was introduced into mainchain of polyimide (API) for the first time to evaluate the feasibility of replacing petroleum-based aromatic/heterocyclic structures by adenine. Systematic studies showed that the API possesses outstanding solubility, thermal and mechanical properties (glass transition temperature ( T g ): 363 °C, weight residual of 95%: 513 °C (N2 ); 506 °C (Air), tensile strength: 144 MPa). Systematic studies indicated that hydrogen-bonding interaction could be a significant cause of these unique thermal and mechanical properties. Graphical abstract: Synopsis: Adenine is an ideal bio-based alternative structure of petroleum-based aromatic/heterocyclic structures in high-performance polymers. Highlights: Bio-based adenine was introduced into the mainchain of high performance polymers (polyimide) for the first time. The obtained polyimide showed outstanding thermal and mechanical properties. System studies indicate that the outstanding thermal and mechanical properties are related to the hydrogen-bonding interactions.